Vision of objects happens faster and earlier for location than for identity - Christian H. Poth; Werner X. Schneider (iScience)
Summary: Visual perception of objects requires the integration of separate independent stimulus features, such as object identity and location. We ask whether the location and the identity of an object are processed with different efficiency for being consciously recognized and reported. Participants viewed a target letter at one out of several locations that were terminated by pattern masks at all possible locations. Participants reported the location of the target and/or its letter identity. Report performance as a function of the target duration before the mask is enabled to estimate the speed of visual processing and the minimum duration for processing to start. Visual processing was faster and started earlier for spatial location than for object identity, even though the processing of the features was (stochastically) independent. Together, these findings reveal an intrinsic preference of the human visual system for the perceptual processing of space as opposed to visual features such as categorical identity.